The Effect of Palm Kernel Shell Ash and Calcium Sulfate Dihydrate on the Properties of Clay Soil for Road Repair - Debby Endriani; Nova Juliana; Suranto Suranto (Sekolah Tinggi Teknologi Pekanbaru, 2025)
The subgrade around Dusun Paloh 80, Desa Tanjung Rejo, Percut Sei Tuan, Deli Serdang Regency, is a clay-type soil with fine grains and low stability. Therefore, a soil stabilization method must be used to achieve a more stable soil. The purpose of this study was to determine the value of clay soil swelling and the effect of adding palm shell ash and calcium sulfate dihydrate at percentages of 0%, 4%, 6%, 8%, 10% and 12% on the plasticity index and shrinkage limit. Soil stabilization is the mixing of soil with certain materials to improve its technical properties and meet specific requirements. In this study, clay soil stabilization was achieved using palm shell ash and gypsum. Tests were conducted based on the ASTM method. The largest swelling occurred at 12% in a 14-day soaking at 13.08%, and the smallest at 12% in a 1-day soaking at 0.57%. The correlation between the plasticity index and the swelling limit is that the greater the plasticity index, the greater the swelling; meanwhile, the greater the shrinkage limit, the smaller the swelling.